A retrospective study of efficacy and cost efficiency of medical vs. surgical management of abortions in first trimester - Agarwal, Meetangi; Ramanujam, Sailatha; Ramachandran, Anuradha C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aim of the study was to assess and comparatively evaluate the efficacy of different methods of first trimester abortions (medical, surgical) in terms of its safety, cost and effectiveness. Methods: We present a retrospective observational research study done at Chettinad hospital and research institute, Kelambakkam Chennai which included a total of 70 patients of first trimester abortions, in the period from June 2019 to June 2020. 55 patients were offered medical treatment (MTOP) and were followed up with a repeat scan after 2 weeks. In cases of failed medical abortion patient underwent curettage. Though, in some cases after an attempt at medical abortion, if the products didn’t expel at all within 48 hours, dilatation and evacuation was offered. Transvaginal ultrasound was performed to confirm the success of the treatment. In 15 cases who presented with incomplete abortion, surgical treatment (STOP) was offered. The outcomes considered were successful complete abortions, failed medical abortions, side effects and complications including blood transfusion. Results: The baseline characteristics of women were similar in both the groups like mean age, parity, history of previous termination of pregnancy (TOP). The success rate in MTOP was 67.2% and in STOP 100%.The amount of bleeding experienced was moderate to heavy in MTOP and minimal to moderate in STOP.37 women who underwent only medical termination who returned for the 2-week follow-up, the rate of complete pregnancy termination was 94% and for the remaining 2 women surgical intervention was required. In the surgical group, at the 2-week follow up, no woman underwent a repeat vacuum aspiration with an efficacy of 100%. No significant difference was found in the mean total cost for the medical and surgical groups after adding the subsequent costs (including additional manual vacuum evacuation). Conclusions: Medical termination of abortion should be preferred over surgical termination as it is safer, cost effective, with fewer complications and high success rate.